Treatment of rheumatoid arthritis using dual-targeted and dual-response intelligent micelles: a “three birds with one stone” strategy - Rui-Bo Guo; Lu Zhang; Yang Liu; Liang Kong; Yang Yu; Bin Yang; Zuo-Jun Wang; Jing-Yi Zhang; Xue-Tao Li (Journal of Nanobiotechnology)
Abstract Rheumatoid arthritis (RA) is an autoimmune disease whose pathophysiology is closely related to inflammation-associated cells and the microenvironment of inflamed joints. This study aimed to develop dual-targeted, reactive oxygen species (ROS)/pH dual-responsive, size-shrinkable intelligent micelles targeting M1 macrophages and fibroblast-like synoviocytes (FLSs) to enhance drug efficacy and safety. These micelles were surface-modified with PEG5000 to prolong their circulation time in the bloodstream and hide the targeting molecules. The optimized particle size allowed the micelles to reside in inflamed joints through the extravasation through leaky vasculature and subsequent inflammatory cell-mediated sequestration (ELVIS) effect. The high concentration of ROS in the inflamed joint caused the detachment of the hydration layer of PEG5000, which was then specifically recognized and internalized by M1 macrophages and FLSs via CD44 receptor-mediated endocytosis, ultimately allowing the release of the drug into the acidic environment of the inflamed cells. The in vivo and in vitro evaluation showed that micelles precisely targeted the inflammatory site, thus inhibiting the expression of pro-inflammatory cytokines, reversing the polarization of M1 macrophages, inhibiting the invasion and migration of proliferative FLSs, and, at the same time, regulating the seeds and soils of RA. This “three birds with one stone” approach targeted multiple aspects of RA, opening new horizons for comprehensive treatment of RA.